The RGF/GLV/CLEL Family of Short Peptides Evolved Through Lineage-Specific Losses and Diversification and Yet Conserves Its Signaling Role Between Vascular Plants and Bryophytes - Furumizu, Chihiro; Sawa, Shinichiro (Frontiers in Plant Science, 2021)
Short secreted plant peptides act as key signaling molecules and control a plethora of developmental and physiological processes. The ROOT GROWTH FACTOR (RGF)/GOLVEN (GLV)/CLE-Like (CLEL) family of peptides was discovered to be involved in root development in Arabidopsis thaliana. In contrast to active research efforts, which have been revealing receptors and downstream signaling components, little attention has been paid to evolutionary processes that shaped the RGF signaling system as we know it in angiosperms today. As a first step towards understanding how RGF signaling emerged and evolved, this study aimed to elucidate the phylogenetic distribution and functional conservation of RGF-like sequences. Using publicly available, genome and transcriptome data, RGF-like sequences were searched in 27 liverworts, 22 mosses, 8 hornworts, 23 lycophytes, 23 ferns, 38 gymnosperms, and 8 angiosperms. This led to the identification of more than four hundreds of RGF-like sequences in all major extant land plant lineages except for hornworts. Sequence comparisons within and between taxonomic groups identified lineage-specific characters. Notably, one of the two major RGF subgroups, represented by A. thaliana RGF6/GLV1/CLEL6, was found only in vascular plants. This subgroup, therefore, likely emerged in a common ancestor of vascular plants after its divergence from bryophytes. In bryophytes, our results infer independent losses of RGF-like sequences in mosses and hornworts. On the other hand, a single, highly similar RGF-like sequence is conserved in liverworts, including Marchantia polymorpha, a genetically tractable model species. When constitutively expressed, the M. polymorpha RGF-like sequence (MpRGF) affected plant development and growth both in A. thaliana and M. polymorpha. This suggests that MpRGF can exert known RGF-like effects and that MpRGF is under transcriptional control so that its potent activities are precisely controlled. These data suggest that RGFs are conserved as signaling molecules in both vascular plants and bryophytes and that lineage-specific diversification has increased sequence variations of RGFs. All together, our findings form a basis for further studies into RGF peptides and their receptors, which will contribute to our understandings of how peptide signaling pathways evolve.